Efficient Degradation of Iopromide by Using Sulfite Activated with Mackinawite - Yingtan Yu; Ying Lyu; Ting Zhang; Lin Liu; Bing Fan; Jian Wang; Chaoxing Zhang (Molecules, 2021)
Iopromide (IOP), an iodinated X-ray contrast medium (ICM), is identified as a precursor to iodide disinfection byproducts that have high genotoxicity and cytotoxicity to mammals. ICM remains persistent through typical wastewater treatment processes and even through some hydroxyl radical-based advanced oxidation processes. The development of new technologies to remove ICMs is needed. In this work, mackinawite (FeS)-activated sulfite autoxidation was employed for the degradation of IOP-containing water. The experiment was performed in a 500 mL self-made temperature-controlled reactor with online monitoring pH and dissolved oxygen in the laboratory. The effects of various parameters, such as initial pH values, sulfite dosages, FeS dosages, dissolved oxygen, and inorganic anions on the performance of the treatment process have been investigated. Eighty percent of IOP could be degraded in 15 min with 1 g L−1 FeS, 400 μmol L−1 sulfite at pH 8, and high efficiency on the removal of total organic carbon (TOC) was achieved, which is 71.8% via a reaction for 1 h. The generated hydroxyl and oxysulfur radicals, which contributed to the oxidation process, were identified through radical quenching experiments. The dissolved oxygen was essential for the degradation of IOP. The presence of Cl− could facilitate IOP degradation, while NO3− and CO32− could inhibit the degradation process. The reaction pathway involving H-abstraction and oxidative decarboxylation was proposed, based on product identification. The current system shows good applicability for the degradation of IOP and may help in developing a new approach for the treatment of ICM-containing water.